SISTEM INFORMASI PEMBAYARAN SPP BERBASIS WEBSITEPADA SMP STRADA ST. FRANSISKUS XAVERIUS II - Widiawaty, Valentina (2021)
Technology has become a mainstay to facilitate human work. By the use of advanced technology, data processing can be carried out effectively and efficiently. Data processing takes a lot of time and the possibility of processing errors. Processing of the SPP (Tuition Fee of Contribution for the Management of Education) payment information system at the Strada St. Fransiskus Xaverius II Junior High School is still done conventionally. The SPP payment system procedure is being started from the payment process, checking proof of payment, paying SPP, and making a SPP payment report. To overcome these problems, research is carried out using the waterfall method. The waterfall method is used in application development so that the process carried out is a sequence from the problem identification stage to testing. System analysis was carried out using the PIECES method. The procedure of SPP proposal payment system uses process of user account management, login, upload letter of authority, bill management and bill checking as addition. The design is using UML (Unified Modeling Language), User Interface, and database. In this research, a tuition payment information system has been created which makes the current process more efficient and effective. The SPP payment information system is made in the form of a website that can make it easier for users.